PENGARUH PENILAIAN KINERJA TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING (Studi Pada Dinas Pariwisata Kota Batu) - Rochmah, Desi Kurnia (Jurnal Ilmiah Mahasiswa FEB, 2017)
This study aims at analyzing the influence of performance assessment on employee performance at Tourism Office of Batu City through work motivation as the intervening variable. This explanatory research explains the relationÂ  60 between variables being studied. The number of sample is 60 respondents. The data were collected through questionnaires measured using Likert scale. The data were analyzed through descriptive analysis technique and path analysis using smartPLS 3.0. The result of the research show that (1) performance assessment does not directly influence performance; (2) performance assessment directly influences work motivation; (3) work motivation directly influences employee performance; (4) performance assessment indirectly influences employee performance mediated by work motivationKeywords : performance assessment, work motivation, employee performance